GE_GERICHTE P/4950/2019 vom 9. Februar 2022 - GE Cour de justice (2022)
SOUSTRACTION DE DONNÉES(ART. 143 CP);FRAIS DE LA PROCÉDURE;OUVERTURE DE LA PROCÉDURE;ILLICÉITÉ;INDEMNITÉ(EN GÉNÉRAL) | CP.143.al1; CPP.426.al2; CPP.429.al1.leta; CPP.430.al1.leta